Estación integrada de seguridad comunitaria - La Mariscal - Reyes León, David Esteban (2017)
During the ninth semester the students of Project Workshop AR0 960 made an urban plan located in an important centrality of the Metropolitan District of Quito: La Mariscal, which is located on a plain, which links to the Historic Center with the north center from the city Today it is one of the most tourist and economic areas of the city, where its streets and buildings have a great historical and architectural value. So within the urban plan it was important to understand the history of how this urban piece was formed and what the changes were until today. Within the development of the urban plan was worked within four major themes; The morphology, the equipment, the mobility and the public space, through which the different problems of each field of study are identified, the data for the rapid growth of the city among other factors, with which strategies were generated for the urban plan , To be able to return the Vitality and vocation of the sector, without leaving aside the attractiveness that the sector currently has. One of the biggest problems that could be determined was the insecurity and sense of insecurity in the sector. This is especially true at night; Where by the low percentage of residence certain points of the sector after hours of work low its activity. So it was decided to implement within the proposed equipment, a security station. This will be part of the network of security stations distributed in the DMQ.